2023
DOI: 10.3390/nu15020381
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-Processed Food Consumption Is Related to Higher Trans Fatty Acids, Sugar Intake, and Micronutrient-Impaired Status in Schoolchildren of Bahia, Brazil

Abstract: Ultra-processed food (UPF) consumption impacts nutrient intake and plays an important role in non-communicable diseases (NCD), even among schoolchildren. This cross-sectional study aimed to characterize the food consumption of this population and its relationship with laboratory and anthropometric aspects. A sample of 190 subjects aged 5 to 19 y was randomly selected for dietary, laboratory, and anthropometric assessment. Statistical inference was calculated using Spearman’s correlation. Excess weight was obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…In terms of nutrient intake, and in accordance with a previous study, higher consumption of SFA and trans-FA was observed in the group with a greater consumption of UPFs, while the intake of fiber was significantly lower [37]. The differences in the quality of the diet between high UPF and low UPF consumers were also evident when analyzing the urinary levels of polyphenols.…”
Section: Discussionsupporting
confidence: 89%
“…In terms of nutrient intake, and in accordance with a previous study, higher consumption of SFA and trans-FA was observed in the group with a greater consumption of UPFs, while the intake of fiber was significantly lower [37]. The differences in the quality of the diet between high UPF and low UPF consumers were also evident when analyzing the urinary levels of polyphenols.…”
Section: Discussionsupporting
confidence: 89%
“…On the other hand, decreased body fat is more common in PEW than in sarcopenia [ 31 ]. Etiological factors leading to sarcopenia and PEW associated with CKD that are exacerbated by consumption of UPFs include the following: developed insulin resistance, acidosis, vitamin D deficiency, and disruption of hormones like testosterone, insulin growth factor-1 (IGF-1), and growth hormone (GH) resistance [ 32 , 33 ]. In addition, the change in the gut microbiome and dysfunction of the gut barrier aggregated by exposure to phthalates, which leaks into food through contact materials or food processing plastics, leads to the development of an inflammatory environment (increased levels of pro-inflammatory cytokines levels such as tumor necrosis factor-α (TNF-α) and interleukin-6 (IL-6)) [ 34 , 35 ] as a contributor to muscle wasting [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Volunteers rated each item on an intensity scale ranging from 0 to 3, with a maximum possible score of 63 points. The severity of depressive symptoms was categorized as minimal (0-13 points), mild (14)(15)(16)(17)(18)(19), moderate (20)(21)(22)(23)(24)(25)(26)(27)(28), or severe (29-63) using previously established references [59,60].…”
Section: Severity Of Depressive Symptomsmentioning
confidence: 99%
“…Recent literature has shown that processed foods have a negative impact on dietary quality and health due to the poor nutrient density, their high additive content, and association with higher intakes of sugars and trans-fatty acids [14]. Sugar-sweetened beverages and processed meats [14,15] have been associated with an increased risk of non-communicable diseases including colorectal cancer [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation